Some clinical and laboratory predictors of structural changes in the biological shunt after femoral-popliteal bypass surgery - N. G. Khorev; V. I. Kotov; V. O. Konkova (Амбулаторная хирургия)
Introduction. For revascularization in the absence of autovenous material, epoxy-treated bioprostheses from the bovine internal mammary artery are widely used in the Russian Federation, which are subjected to certain structural deformations.Purpose and objectives. To compare the structural changes of the biological prosthesis and autovenes in the long-term period after surgery and to determine the influence of some clinical and laboratory parameters on this process.Materials and methods. The study included 45 patients with isolated occlusion of the superficial femoral artery (PBA), who underwent blood flow restoration using various types of prostheses. The patients were divided into 2 groups: group 1 (main) – 25 patients who underwent femoral-popliteal proximal bypass surgery with epoxy-treated bioprostheses from the bovine internal mammary artery; group 2 (control) – 20 patients who underwent femoral-popliteal proximal bypass surgery with a reversed autovena.Results and discussion. During the follow – up period from 1 year to 8 years, 28% of bioprostheses underwent expansion, and 20.0% of patients with autovena showed narrowing of the shunt. In the main group, males had better biological graft patency (RR = 0.76 CI (0.3 2; 1.77)), but in the control group, the male sex increased the risk of occlusion (RR = 1.25 CI (0.18; 8.77)). When followed up for 5 years, the relative risk of prosthetic expansion decreased. At the same time, in patients of the control group, which is not characterized by ectasia, we revealed a decrease in the relative risk of stenosis. The clinical factor affecting the expansion of the biological prosthesis was type 2 diabetes mellitus.Conclusions. The characteristic structural changes in the separated period (more than a year) for an autovenous conduit are narrowing, and for a biological prosthesis – expansion with the formation of aneurysms.